Genealogies of 'Jews' and 'Muslims': social imaginaries in the race-religion nexus - Jansen, Yolande; Meer, Nasar (Patterns of prejudice, 2020)
In 1942, the French-Jewish philosopher Vladimir Jankélévitch wrote:Among all the fascist impostures, anti-Semitism is not the one that reaches the greatest number of victims, but it is the most monstrous. Perhaps for the first time men are officially tracked down not for what they do, but for what they are. They expiate their ‘being’ and not their ‘having’: not acts, a political opinion or a profession of faith like the Cathars, the Freemasons, or the Nihilists, but the fate of birth.For Jankélévitch, antisemitism confirmed a conceptual configuration that had been developing over the course of several centuries, where ‘race’, ‘religion’ and ‘political opinion’ had each achieved their particular and clearly distinguished status. For ‘being’ there was the category of race, while ‘having’ concerned acts, religious belief and political opinion. Persecution because of one’s being was what in his view illustrated the novelty and specificity of antisemitism as racism. The characterization is an illustration of an early European bifurcation between racisms, omitting as it does how chattel slavery had literally tracked men and women down ‘not for what they do, but for what they are’. This framing was part of a common tendency of not-relating the race-making of one group to another, and, in particular, betrays a focus on Europe ‘itself’ instead of considering Europe a colonial space intimately connected to its exterior. The underlying conceptual scheme that opposes race and religion, being and having, is still a prominent feature of public controversies concerning Islam, religion and secularism in Euro-Atlantic contexts, often centring on the comparability of antisemitism and Islamophobia. The scheme especially defines a distinction between critique of religion (and, therefore, of ‘Islam’), deemed legitimate because it targets opinion, ideology and belief, and racism, in which antisemitism is located. 2 Illustrating this train of thought in an editorial in Charlie Hebdo, editor-in-chief Gérard Biard writes, on 1 March 2017, fourteen months after the murder of his colleagues:Islamophobia has been conceptualised on the basis of a deliberately vicious postulate: critiquing Islam is insulting all Muslims. Antisemitism, by contrast, hits the Jews without distinction, whether they are believers or atheists, stick to religious practices or do not. It has as a target human beings for what they are, not for what they think or believe. Islam is a religious and political doctrine, that even implies a societal project. It is something that one chooses, or that one sees imposed on oneself. Such a thing can be the target of critique, but not of racism. Critique of a doctrine, of its rules, symbols and of those who promote them is perfectly legitimate in a democracy. It is even one of its foundations. So let’s talk about the real problem and ask a real question: those who do not stop talking of Islamophobia, do they desire to finish with democracy?